Hypoglycemic potential of Elaeagnus angustifolia fruit polysaccharide on streptozotocin-induced type 2 diabetic mice (Bangladesh Journal of Pharmacology, 2018)
In this study, the hyperglycemic potential of Elaeagnus angustifolia fruit polysaccharide in both normal healthy and streptozotocin-induced diabetic mice was investigated. Results showed no significant effect of E. angustifolia fruit polysaccharide on blood glucose level in normal control group, while E. angustifolia significantly suppressed the rise in blood glucose of diabetic mice. In addition, in the first two weeks of administration, the body weight was decreased both in negative control group and E. angustifolia groups, however, E. angustifolia  (800 mg/kg) was recovered to the began weight in the fourth week. E. angustifolia (800 mg/kg) could markedly reduce the levels of total cholesterol, triglyceride and improve the level of high density lipoprotein-cholesterol. The results suggest that E. angustifolia could be considered as an ingredient of functional foods for diabetes.Video Clip of Methodology:10 min 19 sec   Click to watch